Academic formation and permanent education: influences on leadership styles of nurses Formação acadêmica e educação permanente: influências nos estilos de liderança de enfermeiros - Karen Cristina Kades Andrigue; Leticia de Lima Trindade; Simone Coelho Amestoy (Universidade Federal do Estado do Rio de Janeiro, 2017)
Objetivo: conhecer as influências da formação acadêmica e da Educação Permanente em Saúde (EPS) nos estilos de liderança adotados pelos enfermeiros no âmbito hospitalar. Método: pesquisa qualitativa do tipo descritiva, apoiada no referencial de Hersey e Blanchard. Participaram do estudo seis enfermeiros da rede hospitalar de Chapecó (SC), que tipificavam diferentes estilos de liderança. Os dados foram coletados por meio de entrevistas semiestruturadas e analisados conforme Análise Temática. Resultados: os participantes sentiram-se pouco influenciados para liderar diante da formação obtida na graduação e ressaltaram dificuldades de integração ensino-serviço, que interferiram no exercício da liderança. Quanto à EPS, sinalizaram a falta de investimentos na qualificação. Conclusão: destaca-se a importância de o ensino na graduação fortalecer as práticas de aprendizagem da liderança e entende-se que a liderança é aperfeiçoada ao longo da vida profissional.    Objective: to know the influences of academic training and Continuing Health Education (EPS) on the leadership styles adopted by nurses in the hospital environment. Method: it is qualitative descriptive-type research supported in the references of Hersey and Blanchard. Six nurses from the hospital network of Chapecó, Santa Catarina, participated in this study and typified different leadership styles. The data were collected through semi-structured interviews and analyzed according to Thematic Analysis. Results: the participants felt only slightly influenced to lead during the training obtained in their graduation course and highlighted difficulties in integrating education service, which interfered in exercising leadership. As for the Continuing Health Education (EPS), it indicated a lack of investment in qualification. Conclusion: standing it was highlighted the importance of education in graduation studies to strengthen leadership learning practices and it is understood that leadership is perfected and improved throughout working life. Key words: Nursing, Leadership, Continuing Education.